2019
DOI: 10.1088/2058-6272/ab2136
|View full text |Cite
|
Sign up to set email alerts
|

Symmetry transformations for magnetohydrodynamics and Chew–Goldberger–Low equilibria revisited

Abstract: Being motivated by the paper [O. I. Bogoyavlenskij, Phys. Rev. E 66, 056410 (2002)] we generalise the symmetry transformations for MHD equilibria with isotropic pressure and incompressible flow parallel to the magnetic field introduced therein in the case of respective CGL equilibria with anisotropic pressure. We find that the geometrical symmetry of the field-aligned equilibria can break by those transformations only when the magnetic field is purely poloidal. In this situation we derive three-dimensional CGL… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…In addition, we have shown that, if a given equilibrium with field-aligned incompressible flows of constant mass density and constant pressure anisotropy function fulfils the aforementioned condition, and therefore is linearly stable, then all the families of equilibria obtained by the application of the symmetry transformations presented in Evangelias & Throumoulopoulos (2019) to the original equilibrium, are also linearly stable, provided that a parameter, C, appearing in these transformations, is positive-definite.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…In addition, we have shown that, if a given equilibrium with field-aligned incompressible flows of constant mass density and constant pressure anisotropy function fulfils the aforementioned condition, and therefore is linearly stable, then all the families of equilibria obtained by the application of the symmetry transformations presented in Evangelias & Throumoulopoulos (2019) to the original equilibrium, are also linearly stable, provided that a parameter, C, appearing in these transformations, is positive-definite.…”
Section: Discussionmentioning
confidence: 90%
“…In a recent work (Evangelias & Throumoulopoulos 2019) a set of symmetry transformations that map anisotropic plasma equilibria with field-aligned incompressible flows was introduced; specifically, these transformations, when applied to a given equilibrium with parallel incompressible flow and anisotropy function, σ d , uniform on the magnetic surfaces labelled by the function ψ, {B, (ψ), V = λB/( √ µ 0 ), P, σ d (ψ)}, produce an infinite family of respective equilibria with field-aligned incompressible flows, but a density and anisotropy function that may vary on the magnetic surfaces, {B 1 , 1 , V 1 , P 1 , σ d 1 }. These transformations are defined by…”
Section: Stability Under Symmetry Transformationsmentioning
confidence: 95%
See 1 more Smart Citation
“…Then we construct 3D equilibria by applying the introduced transformations to a known class of axisymmetric equilibria. The results presented in Chapter 4 were published in [168]. In Chapter 5 we derive a sufficient condition for the linear stability of plasma equilibria with incompressible flow parallel to the magnetic field, constant mass density and pressure anisotropy, such that the pertinent anisotropy function remains constant.…”
Section: Thesis Objectives and Outlinementioning
confidence: 99%